DAMPAK PERKEMBANGAN KAWASAN PESISIR TERHADAP PERUBAHAN FUNGSI LAHAN DAN KESEJAHTERAAN PETANI TAMBAK DI PESISIR TELUK KENDARI - Muhammad Aswar Limi; La Sara; Taane La Ola; Lukman Yunus (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
The purpose of this study was to determine the impact of the development of coastal areas to changes in land use in the Coastal Kendari Bay and to determine the level of welfare of fish farmers in the Coastal Kendari Bay. The study was conducted in May-August 2016 for the coastal Kendari Bay and in the District Poasia Kendari. The location determination is done deliberately. Population and sample family head fish farmers in the district Poasia Kendari City by 11 households. The samples were conducted census of all the population used as a sample. Data analysis using descriptive analysis to determine the impact of the development of coastal areas to changes in land use and analysis of the revenue that will be used to determine the level of welfare of fish farmers. Based on the results of the study it can be concluded that the development of coastal areas, especially the development of infrastructure in the coastal kendari bay has resulted in a change of land use and land cover in coastal Kendari Bay where the land area of 205.5 ha of ponds decreases were converted into residential areas so that the settlement area and broader become 674.37 Ha and public space increased to 18.46 Ha. Land use resulted in the preservation of the coastal region of Kendari Bay decreased and high sedimentation rate causes changes in the environment and impacted upon the fishery resource and land productivity decreases and affect fish farmers income. The welfare of fish farmers are still determined by the coastal region of Kendari Bay so that fish farmers have a level of prosperitythat is relatively poor.